Study and formulation of standards for intelligent management system of coal mine gas extraction and water exploration operations - SUN Jiping; GONG Dali (Gong-kuang zidonghua)
Gas extraction and water exploration operations are the main measures for the prevention and control of gas and water hazards in coal mines. At present, these operations face challenges such as non-compliance with design plans, ineffective supervision, and substandard borehole quality. The intelligent management system for gas extraction and water exploration leverages AI-based image recognition technology to automatically detect borehole depth, thereby reducing the occurrence of gas and water accidents. ① Based on the operational requirements of gas extraction and water exploration in coal mines, it was proposed that the target identification accuracy should be no less than 95%, and the target recall rate should be no less than 95%. ② According to the workflow of gas extraction operations in coal mines, it was proposed that the intelligent management system for gas extraction should include functions such as gas geological modeling, extraction borehole design, construction planning, borehole operation, borehole acceptance, borehole record management, pipeline management, parameter monitoring, mine environment monitoring, extraction compliance evaluation, and prediction of absolute gas emission. It should also provide capabilities including but not limited to display, query, storage, and alarm function. Based on the operational needs of gas extraction, it was proposed that the system was also expected to provide auxiliary borehole design based on extraction methods, dispatch of construction plans, receipt of borehole operation plans by on-site devices, automatic calculation of borehole depth, and final acceptance of gas extraction boreholes. It was further proposed that documentation such as extraction design statements for working faces, safety technical measures, original shift reports, final acceptance forms for gas extraction boreholes, complete extraction borehole operation videos, and videos of each drilling process should be retained for at least two years. ③ According to the workflow of water exploration operations in coal mines, it was proposed that the intelligent management system should include functions such as "three-special management", geophysical survey management, drilling design, drilling planning, drilling operation, drilling acceptance, drilling analysis, and drilling ledger management, with capabilities for display, query, storage, and alarm functions. Based on the operational needs of water exploration, it was proposed that the system should provide auxiliary borehole design based on anomalous geophysical zones, dispatch of drilling plans, reception of borehole operation plans by on-site devices, automatic calculation of borehole depth, acceptance of individual boreholes and overall drilling projects, and big data analysis applications. It was also proposed that the system should support entry and exit logging of dedicated water exploration personnel and enable real-time tracking of their location during operations. The system was also expected to display real-time methane sensor readings from the operation site. It was proposed that documentation such as geophysical survey and drilling design documents, safety technical measures, excavation suspension notices, water exploration notices, original shift reports, drilling project acceptance forms, safety confirmation handover forms, excavation approval notices, drilling project summaries, monthly/quarterly/annual water exploration statistics, complete drilling operation videos, single-hole operation videos, and videos of each drilling rod process should be retained for at least two years.